Measurement of criteria parameters of analog-to-digital converters and monitoring of their changes during the radiation experiment - Roman S. Torshin; Georgy S. Sorokoumov; Dmitry V. Bobrovsky; Alexander A. Demidov; Anastasya V. Ulanova (Безопасность информационных технологий, 2020)
The paper presents a method for testing ADC, intended for measurement the basic parameters of converters by histogram test (or code density test). This method is ideally suited for modern wide bandwidth high precision ADCs and is universally accepted, especially with the proliferation of standard PC-based software and ADC manufacturer’s evaluation boards. The histogram and Fast Fourier transform (FFT) tests use essentially the same hardware, both are normally part of a comprehensive ADC test plan [1]. Modular Instrumentation System PXI of NI and Signal Generator SMA100B (ROHDE & SCHWARZ) were used as test equipment for the tests. The basic static and dynamic parameters of the ADC AD7888 were calculated using this method. The degradation of the main parameters of the ADC AD7888 under the influence of the absorbed dose at the «RIK-0401» x-ray unit is presented in the paper.